Emerging Role of Mesenchymal Stromal Cell-Derived Extracellular Vesicles in Pathogenesis of Haematological Malignancies - Juçara Gastaldi Cominal; Maira da Costa Cacemiro; Belinda Pinto-Simões; Hans-Jochem Kolb; Kelen Cristina Ribeiro Malmegrim; Fabíola Attié de Castro (Hindawi Limited, 2019)
Homoeostasis of bone marrow microenvironment depends on a precise balance between cell proliferation and death, which is supported by the cellular-extracellular matrix crosstalk. Multipotent mesenchymal stromal cells (MSC) are the key elements to provide the specialized bone marrow microenvironment by supporting, maintaining, and regulating the functions and fate of haematopoietic stem cells. Despite the great potential of MSC for cell therapy in several diseases due to their regenerative, immunomodulatory, and anti-inflammatory properties, they can also contribute to modulate tumor microenvironment. The extracellular vesicles that comprise exosomes and microvesicles are important mediators of intercellular communication due to their ability to change phenotype and physiology of different cell types. These vesicles may interact not only with neighbouring cells but also with cells from distant tissues to either maintain tissue homoeostasis or participate in disease pathogenesis. This review focuses on the current knowledge about the physiological role of MSC-extracellular vesicles, as well as their deregulation in haematological malignancies and their potential applications as biomarkers for diagnosis, progression, and treatment monitoring of such diseases.